2005
DOI: 10.1029/2005jc003018
|View full text |Cite
|
Sign up to set email alerts
|

Offshore controls on nearshore rip currents

Abstract: [1] The rip current field resulting from the transformation of surface gravity waves over offshore submarine canyons is studied. Employing a wave transformation model and a wave-induced circulation model over observed bathymetry we find that wave height variations associated with undulations in the canyon contours cause rip current circulation cells with alongshore spacing of O(100m) even though the nearshore bathymetry displays no variations at these length scales. Further, the predicted rips correspond to ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
59
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 19 publications
7
59
0
Order By: Relevance
“…Previous studies also have shown that nearshore circulation, including the locations of rip currents, can be controlled by nonuniformities in the offshore (i.e., outside the surfzone) bathymetry [Long and Ö zkan-Haller, 2005]. Here, the effect of strong alongshore variations in the incident wavefield (caused by an offshore submarine canyon [Long and Ö zkan-Haller, 2005;Magne et al, 2007;Thomson et al, 2007]) on setup and on alongshore flows in the surfzone is examined using field observations and simplified one-and two-dimensional momentum balances. After the theories are outlined (section 2) and the observations are described (section 3), the results are presented (section 4) and conclusions are given (section 5).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies also have shown that nearshore circulation, including the locations of rip currents, can be controlled by nonuniformities in the offshore (i.e., outside the surfzone) bathymetry [Long and Ö zkan-Haller, 2005]. Here, the effect of strong alongshore variations in the incident wavefield (caused by an offshore submarine canyon [Long and Ö zkan-Haller, 2005;Magne et al, 2007;Thomson et al, 2007]) on setup and on alongshore flows in the surfzone is examined using field observations and simplified one-and two-dimensional momentum balances. After the theories are outlined (section 2) and the observations are described (section 3), the results are presented (section 4) and conclusions are given (section 5).…”
Section: Introductionmentioning
confidence: 99%
“…Munk and Traylor, 1947;Shepard and Inman, 1950). The refractive scattering from these canyons induces longshore variations in both wave height and wave breaking, which in turn quite often lead to rip currents (for a recent analysis see Long and Ö zkan-Haller, 2005). Hence, the scattering can play an important role in the nearshore dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Wave breaking on alongshore-nonuniform beaches can drive rip current circulation patterns and spatial variations in breaking-wave-driven alongshore flows [Sonu, 1972;MacMahan et al, 2010;Houser et al, 2013;Winter et al, 2014]. The alongshore gradients in wave breaking and setup that drive rip currents may be generated by local bathymetric variations [Bowen and Inman, 1969;Brander and Short, 2001;Haas et al, 2003;MacMahan et al, 2005Bruneau et al, 2009;Austin et al, , 2014, offshore bathymetric variations [Long and Özkan-Haller, 2005], wave-wave interactions [Dalrymple, 1975;Peregrine, 1998;Buhler and Jacobson, 2001], or wave-current interactions [Dalrymple and Lozano, 1978]. In both field and laboratory studies the speed of rip currents near inhomogeneous bathymetry varies with incident wave properties, tidal elevation, and the geometry of the bathymetric depression [Brander and Short, 2001;Bruneau et al, 2009;.…”
Section: Introductionmentioning
confidence: 99%